A Pharmaceutical Study of Rasasindoora in Perspective of Different Time Pattern (International Journal of Ayurveda and Pharma Research, 2024)
In the system of Ayurveda, there are two basic categories of medicinal formulations-Kashtaushadhi (pure herbal) and Rasaushadhi (herbo-mineral). The standardization of Rasaushadhies through modern parameter gives an easy acceptance and can remove the negative propaganda about medicine containing Parada (mercury). Rasasindoora is widely prepared and clinically practiced by Ayurvedic fraternity. Aims and Objectives: The current study is planned to established the best pharmaceutical method of Rasasindoora in perspective of time and cost. Materials and Method: 250gm Kajjali was taken in every bach for the preparation of Rasasindoora by using EMF (electric muffle furnace) with the thought it gives desired and standard yield. In this study 3 batches of Rasasindoora were prepared in 16 hours, 11 hours and 8 hours. Result: Rasasindoora yield from Batch I, Batch II and Batch III are 50.84%, 51.76% and 50.48%. Conclusion: The average yield is 51.02% and yield from batch III (8hrs) is 50.48%, there is no major difference in % yield in all three batches. Thus, the best adopted method for the preparation of Rasasindoora is batch III (8hrs) due to lesser consumption of electricity, coal and time.